Compassionate use of contezolid in a toddler with severe community-acquired pneumonia induced by staphylococcus aureus: a case report and follow-up - Liu, Hui-Ying; Bi, Xiao-Fei; Wang, Ya-Jun; Xie, Feng-Jie; Zhang, Hong; Zhu, Yu-Cheng; Zhang, Yan; Wang, Zhi-Hui; Wu, Di; Meng, Huan; Lin, Yi-Lu; Liu, Lin-Qiong; et al. (Frontiers in Pediatrics, 2024)
Background: Initial choices of antimicrobial therapy for most cases of community-acquired pneumonia (CAP) in children under 5 years of age are typically based on local epidemiology, risk factors assessment, and subsequent clinical parameters and positive cultures, which can lead to the underdiagnosis and underestimation of lung infections caused by uncommon pathogens. Contezolid, an orally administered oxazolidinone antibiotic, gained approval from the National Medical Products Administration (NMPA) of China in June 2021 for managing complicated skin and soft tissue infections (cSSTI) caused by staphylococcus aureus (SA), streptococcus pyogenes, or streptococcus agalactis. Owing to its enhanced safety profile and ongoing clinical progress, the scope of contezolid's clinical application continues to expand, benefiting a growing number of patients with Gram-positive bacterial infections. Case summary: In this report, we present the first use of contezolid in a toddler with severe CAP caused by SA, aiming to avoid potential adverse drug reactions (ADRs) associated with vancomycin and linezolid. Conclusion: Although contezolid has not been officially indicated for CAP, our case demonstrates its effective and safe application in treating severe CAP caused by SA in a toddler, suggesting the need for further research to expand its therapeutic potential, especially for patients susceptible to or intolerant of ADRs associated with first-line anti-methicillin-resistant staphylococcus aureus (MRSA) antimicrobial agents.